Access to justice by refugees and asylum seekers in South Africa - Okpechi, Abiola (Department of Public Law, 2015)
Premised on the fact that access to justice is essential, if rights are to be actually enjoyed, this thesis set out to examine the extent to which refugees and asylum seekers are able to access justice in South Africa, both for the enforcement of their rights and to settle disputes or other interests at law. In doing this, the thesis examines the obligations that South Africa owes to refugees and asylum seekers on access to justice, and how it gives effect to those obligations.